Paradigm shift in soil fertility ratings for sustainable crop production and environmental quality - Rajendiran, S; Dotaniya, M L; Coumar, M Vassanda (Indian Farming, 2020)
Fertilizers are one of the key inputs for enhancing crop production. However, improper and inadequate application of fertilizers leads to decline in crop productivity and loss of costly fertilizer inputs. Therefore, a paradigm shift in current soil fertility rating and management is need of the hour to overcome these problems. Use of soil fertility ratings with nine classes is being recommended for a particular farm and for a region through modified nutrient index (NI9) to narrow down the variation in the particular fertility category. Further, fertilizer recommendations based on this modified ratings will help in judicious use of fertilizers as well as meet the nutrient demand of the crops. This can be used as alternative to STCR based recommendations, because of the complications experienced during practical field applications of the later.